THE EMERGENCE AND DEVELOPMENT OF JADIDISM, THE HISTORICAL CONDITIONS AND MAIN FIGURES OF THE JADIDISM MOVEMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the modern world, a task has become urgent that requires military personnel to develop new training methods aimed at the comprehensive development of the individual. The military education system sets itself the task of training professional personnel with high personal qualities, qualities, discipline, as well as the ability to make decisions in uncertain and difficult conditions. From this point of view, the Jadidist-reform movement, which played an important role in updating education systems in countries at the beginning of the 20th century, is of particular interest. Integrating the principles of Jadidism is expected to enhance my students' educational attainment by developing critical thinking skills, responsibility, and self-mobilization.